Update on fluid biomarkers for concussion. (18th February 2016) - Zetterberg, Henrik; Morris, Huw R; Hardy, John; Blennow, Kaj
Concussions are difficult to diagnose and symptoms may not appear immediately. As an accurate initial diagnosis has profound implications for the clinical management, there is an unmet need for better diagnostic tools. Fluid biomarkers for CNS injury may represent such tools. These markers are often proteins, peptides or other molecules with selective or high expression in the brain, which can be measured in the cerebrospinal fluid or blood as they leak out or get secreted into the biofluid in response to the injury. Here, we review the literature on fluid markers of neuronal, axonal and astroglial injury and response mechanisms to diagnose CNS injury upon head impact and to determine when the injurious process has resolved.